2020
DOI: 10.1111/1468-5973.12320
|View full text |Cite
|
Sign up to set email alerts
|

Effects of threat and efficacy messages on expected adherence to decontamination protocols in an immersive simulated chemical incident: A randomized controlled experiment

Abstract: The UK’s Initial Operational Response (IOR) decontamination protocol requires that chemically contaminated casualties remove contaminated clothing (disrobe) and then apply water or absorbent materials to skin. The health‐protective efficacy of the protocol is predicated on casualties quickly accepting both the need to act and the fact that this protocol is an effective action. The aim of this study was to test whether adherence is affected by the presentation of information by first responders about the severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“… 32 Subsequent research has demonstrated that effective engagement with the decontamination procedure is also increased when casualties perceive the effectiveness of the measures. 33 …”
Section: Adherence To the Required Public Health Behavioursmentioning
confidence: 99%
“… 32 Subsequent research has demonstrated that effective engagement with the decontamination procedure is also increased when casualties perceive the effectiveness of the measures. 33 …”
Section: Adherence To the Required Public Health Behavioursmentioning
confidence: 99%
“…Studies that have examined casualty experiences and behaviour during decontamination [ 42 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ] have suggested the way in which emergency responders manage an incident will affect the nature of the relationship between responders and members of the public, influencing how members of the public behave [ 67 ] and effecting the outcomes from the incident. Specifically, if emergency responders manage an incident effectively, members of the public will identify with them around a shared goal of undergoing decontamination [ 63 , 65 , 66 ]; this will result in increased public cooperation and compliance during the decontamination process [ 62 , 63 , 65 ].…”
Section: Key Findings From Mass Casualty Decontamination Researchmentioning
confidence: 99%
“…Responders should: Communicate openly and honestly, providing regular updates about the nature of the incident and the actions that they are taking. Providing this information increases perceptions that responders are managing an incident in a fair and legitimate way and increases public willingness to comply with decontamination [ 42 , 63 , 65 , 66 , 68 ]. Communicate in a health-focused way about the need for decontamination.…”
Section: Key Findings From Mass Casualty Decontamination Researchmentioning
confidence: 99%
See 2 more Smart Citations